Erythrocytapheresis for chronic transfusion therapy in sickle cell disease: survey of current practices and review of the literature. Issue 11 (19th October 2016) - Kelly, Shannon; Quirolo, Keith; Marsh, Anne; Neumayr, Lynne; Garcia, Alicia; Custer, Brian
Abstract : BACKGROUND: Chronic red blood cell (RBC) transfusion therapy (CTT) is an integral component of the management of severe sickle cell disease (SCD) and can prevent complications, such as stroke. RBC units can be administered via simple transfusion or exchange transfusion, and erythrocytapheresis (automated RBC exchange transfusion [aRBX]), is increasingly used for CTT. Comparisons of simple and aRBX transfusions are limited, and the current scope of aRBX use is not known. STUDY DESIGN AND METHODS: We administered a survey to define current transfusion practices for CTT and performed a review of the erythrocytapheresis literature. The survey was disseminated to 62 SCD centers, and 31 institutions responded. RESULTS: Collectively, 1274 of 12, 644 patients (10.1%) received CCT, including 929 of 9324 children (10.0%) and 345 of 3320 adults (10.4%). The most common indication for CTT in children was a risk of stroke (86.8%), defined by abnormal transcranial Doppler, previous stroke, or abnormal brain imaging; whereas the most common indications in adults were previous stroke (37.5%) and recurrent/severe pain (29.0%). Simple transfusion was the most common method for children (480 of 919 children; 52.2%) followed by aRBX (344 of 919 children; 37.4%); whereas, in adults, aRBX was more common (180 of 345 adults; 52.2%) than simple transfusion (102 of 345 adults; 29.6%). A smaller percentage of patients received transfusion via manual exchange (7.2% of children and 16.5% of adults) or a combination of methods. CONCLUSIONS: The current literature review was conducted to summarize reported methods, outcomes, and adverse effects with aRBX. Comparisons between chronic simple and aRBX transfusions were included when possible, and areas warranting further study are highlighted.